Measuring and Assessing Fluctuating and Authentic–Durable Happiness in Italian Samples - Monacis, Lucia (Int J Environ Res Public Health, 2021)
On the basis of the self-centeredness and selflessness model, a new instrument assessing two distinct dimensions of happiness, fluctuating and authentic–durable, was developed. The current research aimed at examining the factor structure of the Italian version of the instrument, its psychometric properties and construct validity. To this end, two studies were carried out. Study 1 (N = 544) examined different measurement models, from unidimensional to multidimensional, from a fully symmetrical bifactor solution to a bifactor (S-1) solution. Findings indicated better and adequate fit indices for the last model. Using various samples (n = 1274) Study 2 confirmed the bifactor (S-1) structure and analysed psychometric properties, convergent and divergent validity and temporal stability of the instrument. Findings generally gave evidence of the multidimensional conceptualization of the construct, good levels of reliability values and adequate convergent validity of both scales. Discriminant validity showed mixed results from no association of age with authentic–durable happiness to weak and negative association with fluctuating happiness. Test–retest reliability displayed an adequate value of correlation coefficient for the two set scores of the authentic dimension and a value below the recommended cut-off criteria for the fluctuating dimension, where significant differences in the mean scores emerged. Future studies should aim to replicate the results of this research and attempt to overcome its limitations.